2008
DOI: 10.1097/inf.0b013e31815c1b07
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neonatal Parechovirus Infection and Similarity With Enterovirus Infection

Abstract: It is not possible to distinguish neonatal PeV from EV infection on the basis of clinical signs. Neonates with PeV or EV infection present with sepsis-like illness and the most frequent signs are fever, seizures, irritability, rash, and feeding problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
140
3
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 22 publications
14
140
3
5
Order By: Relevance
“…Therefore, due to the large number and types of viruses, identifying and deciphering the mechanism by which viral infection induces seizures have been challenging. For example, two members of the family Picornaviridae, Enterovirus (EV) and Parechovirus (PeV), have been shown to induce seizures in infected children; however, the available diagnostic tests for EVs do not detect PeVs (2,3). A recent retrospective study, using pediatric cerebrospinal fluid samples previously screened for EV, demonstrated that the inclusion of a novel PeV-specific PCR assay led to a 31% increase in the detection of viruses causing virally induced CNS symptoms and neonatal sepsis (4).…”
mentioning
confidence: 99%
“…Therefore, due to the large number and types of viruses, identifying and deciphering the mechanism by which viral infection induces seizures have been challenging. For example, two members of the family Picornaviridae, Enterovirus (EV) and Parechovirus (PeV), have been shown to induce seizures in infected children; however, the available diagnostic tests for EVs do not detect PeVs (2,3). A recent retrospective study, using pediatric cerebrospinal fluid samples previously screened for EV, demonstrated that the inclusion of a novel PeV-specific PCR assay led to a 31% increase in the detection of viruses causing virally induced CNS symptoms and neonatal sepsis (4).…”
mentioning
confidence: 99%
“…It can cause systemic infections with possible neurological involvement in infants, which are collectively described as 'sepsis-like illnesses' [98,99,104]. Such illnesses typically present with fever, seizures, irritability, respiratory and gastrointestinal problems, and occasional rash, and are indistinguishable from severe EV infections [34,105]. The fraction of symptomatic HPeV-3-infected infants that develop sepsis-like illness can exceed 80 %; most such patients require hospitalization and up to one-third of them are admitted to the ICU [104][105][106].…”
Section: Human Parechovirusmentioning
confidence: 99%
“…Infection of meningeal cells or cells of the ventricular lining results in aseptic meningitis -a non-bacterial inflammation of tissues lining the brain [33]. Infection of neurons with subsequent inflammation of brain parenchyma results in encephalitis, which can have long-term sequelae or be fatal [34]. Inflammation of the spinal cord grey matter results in myelitis and can lead to limb paralysis [33].…”
Section: Picornavirus Cns Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…C-reactive protein remains low or slightly elevated (Pineiro et al, www.intechopen.com 2010; Verboon-Maciolek et al, 2008b; own observations). In some cases liver enzymes can be elevated, sometimes leading to hepatitis and liver necrosis (Levorson et al, 2009;Selvarangan et al, 2011;Verboon-Maciolek et al, 2008b).…”
Section: Laboratory Findings and Diagnosis Of Hpev Infectionmentioning
confidence: 99%